Analisis Faktor Turnover Karyawan Pada PT HM Tangerang - Raissa Arham Delyuzar; Kartika Anjeli Tambunan; Astriyani Sandya Paramita (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
Employee turnover is the frequency of which employees leave a company and replaced by new employees within a certain period. In this study, the problem was the high number of resignations among PT HM Tangerang employees, which is caused by low compensation and uncomfortable work environment. Therefore, this study aims to examine and analyze the impact of compensation and work environment on employee turnover among PT HM Tangerang employees. This study was conducted from January to June 2025. The research method used was Field Study and Literature Study. The population of this study consisted of all employees who had left in 2023-2024 from PT HM Tangerang, with a total of 94 employees. The sampling technique in this study is the Slovin Formula with a margin error of 10%, thus the sample size in this study was 50 contract employees who resigned. The research method used was a quantitative method with Structural Equation Modeling – Partial Least Square (SEM-PLS) analysis.